Advances in the etiology of sweet potato (Ipomoea batatas (L.) Lam) yellow curling disease in Argentina - Flamarique, Sofía Solange; Vilanova Perez, Antonella; Luque, Andres Vicente; Rodriguez Pardina, Patricia; Di Feo, Liliana Del Valle (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2022)
Sweet potato yellow curling (YC), the most severe disease of sweet potato detected in Argentina, causes symptoms and damage to sweet potato crops in all cultivated regions. Since 2010/11, the presence of four viruses has been detected in symptomatic cv. Arapey INIA: two potyviruses non-persistently transmitted by Myzus persicae (sweet potato feathery mottle virus, SPFMV and sweet potato virus G, SPVG); a closterovirus, sweet potato chlorotic stunt virus (SPCSV) and a geminivirus, sweet potato leaf curl virus (SPLCV), both transmitted by Bemisia tabaci in a semi-persistent and persistent manner, respectively. All the plants were collected from fields in Colonia Caroya, Córdoba province, Argentina. The objectives of the present work are to isolate and identify the virus or viruses involved in YC disease of sweet potato, and to elucidate the viral combination that reproduces YC symptoms. The most severe YC symptoms for this genotype in the field were only reproduced by a combination of the four viruses. The symptoms include chlorosis, stunting, mosaic, blistering, leaf curling, chlorotic spots, chlorotic patterns, leaf area reduction and distortion, and upward curling of leaf edges. The presence of each virus was detected by serological (DAS, NCM and TAS-ELISA) and molecular (PCR) tests. It is concluded that the interaction of SPFMV, SPVG, SPCSV and SPLCV is needed for the development of YC symptoms.